The impact of unemployment benefits on birth outcomes: Quasi-experimental evidence from European linked register data - Kessler, Dorian; Hevenstone, Debra (PLOS ONE, 2022)
Cash transfers have been shown to improve birth outcomes by improving maternal nutrition, increasing healthcare use, and reducing stress. Most of the evidence focuses on programs targeting the poorest in the US—a context with non-universal access to healthcare and strong health inequalities. It is thus unclear whether these results would apply to cash transfers targeting a less disadvantaged population and whether they apply to other contexts. We provide evidence on the impact of unemployment benefits on birth outcomes in Switzerland, where access to healthcare is near-universal and social assistance is relatively generous. Our study taps into a policy reform that reduced unemployment benefits by 56%. We use linked parent-child register data and difference-in-differences estimates as well as within sibling comparisons. We find that the reform did not impact birth outcomes when fathers were unemployed but reduced the birthweight of children when mothers were unemployed by 80g and body length by 6mm. There are stronger effects for children whose mothers were the primary earner before job loss, but effects do not differ systematically by household income. These results suggest that in the Swiss context, unemployment benefits improve birth outcomes by reducing (job search) stress rather than by improving nutrition or healthcare use. As such, cash transfers likely play a role for newborn health in most other contexts.